Liberation From Venoarterial Extracorporeal Membrane Oxygenation: A Review. (July 2021) - Brahmbhatt, Darshan H.; Daly, Andrea L.; Luk, Adriana C.; Fan, Eddy; Billia, Filio
Abstract : Venoarterial extracorporeal membrane oxygenation may be used for circulatory support in cardiogenic shock as a bridge to recovery, a bridge to a ventricular assist device (VAD), or a bridge to transplant. While the determination of potential exit strategies is essential before cannulation, the final determination of a patient's options may change, in part, through their in-hospital clinical course. We propose that liberation from venoarterial extracorporeal membrane oxygenation should be conceptualized as a process of discovery in the assessment of a patient's underlying clinical status and a key driver of further clinical decision-making. A trial of liberation from support should be considered when the goals of the weaning trial are well-defined and, ideally, in the absence of potentially confounding clinical factors. In this review, we will discuss readiness to wean criteria from venoarterial extracorporeal membrane oxygenation, as well as specific clinical, biochemical, and echocardiographic parameters that may prove useful in determining weaning timing and revealing the patient's underlying hemodynamic status and prognosis. The role of various cannula configurations, support devices, and pharmacological adjuncts will also be discussed. Finally, we highlight current gaps in evidence and suggest areas of future research.